EFEKTIVITAS PRILAKU SOSIAL EKONOMI PELAYANAN PUSKESMAS PADA MASYARAKAT MARGINAL DI KOTA MAKASSAR - Calundu, Rasidin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
A qualitative research study with a phenomenological approach found that Public Health Center (Puskesmas) staff in Makassar face various challenges when providing healthcare services to the public, especially those in marginalized groups. Human resource limitations, such as the shortage of medical personnel, force staff to handle a large number of patients within a limited time, which in turn lowers the quality of care. Inadequate infrastructure and facilities, such as limited inpatient rooms and a lack of medical equipment, hinder the ability to provide optimal diagnosis and treatment. Meanwhile, budget constraints make it difficult for Puskesmas to maintain its facilities and provide essential medications to the community. Additionally, the lack of public awareness and understanding of health issues results in many individuals seeking care only when their conditions have worsened. Negative perceptions that equate Puskesmas with low-quality healthcare services may deter people from utilizing these facilities. Furthermore, social and economic problems, such as limited financial resources and difficulty accessing transportation, present barriers for disadvantaged individuals in seeking healthcare. Therefore, it is crucial to foster collaboration among Puskesmas, the government, and the community to improve the quality of healthcare services, particularly for those who need extra attention.